2020
DOI: 10.1371/journal.pgen.1008774
|View full text |Cite
|
Sign up to set email alerts
|

Pax6 organizes the anterior eye segment by guiding two distinct neural crest waves

Abstract: Cranial neural crest (NC) contributes to the developing vertebrate eye. By multidimensional, quantitative imaging, we traced the origin of the ocular NC cells to two distinct NC populations that differ in the maintenance of sox10 expression, Wnt signalling, origin, route, mode and destination of migration. The first NC population migrates to the proximal and the second NC cell group populates the distal (anterior) part of the eye. By analysing zebrafish pax6a/b compound mutants presenting anterior segment dysg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 76 publications
(104 reference statements)
1
26
0
Order By: Relevance
“…Fate mapping studies in mice have shown that both NC and mesoderm contribute to the corneal stroma and corneal endothelium, while in chick, both of these corneal structures as well as the iris stroma are NC derived ( Gage et al, 2005 ). Time-lapse imaging of pre- and post-migratory NC cells in zebrafish embryos has shown at least three waves, including two distinct Sox10 - positive and one Foxd3-positive cell populations ( Eason et al, 2017 ; Takamiya et al, 2020 ). Sox10-positive cells migrate early after optic cup formation and preliminary fate mapping studies show minimal contributions to the adult eye (unpublished data).…”
Section: Anterior Segment Development: Emergence Of the Ocular Neuralmentioning
confidence: 99%
See 2 more Smart Citations
“…Fate mapping studies in mice have shown that both NC and mesoderm contribute to the corneal stroma and corneal endothelium, while in chick, both of these corneal structures as well as the iris stroma are NC derived ( Gage et al, 2005 ). Time-lapse imaging of pre- and post-migratory NC cells in zebrafish embryos has shown at least three waves, including two distinct Sox10 - positive and one Foxd3-positive cell populations ( Eason et al, 2017 ; Takamiya et al, 2020 ). Sox10-positive cells migrate early after optic cup formation and preliminary fate mapping studies show minimal contributions to the adult eye (unpublished data).…”
Section: Anterior Segment Development: Emergence Of the Ocular Neuralmentioning
confidence: 99%
“…Animal models have shown that Pax6 targets essential extracellular signaling molecules that control multiple steps in eye morphogenesis ( Cvekl and Callaerts, 2017 ). Pax6 is initially expressed in the optic pit and subsequently in the optic vesicle, optic stalk and overlying surface ectoderm ( Enwright and Grainger, 2000 ; Grocott et al, 2011 ; Cvekl and Callaerts, 2017 ; Takamiya et al, 2020 ). Pax6 is important for optic stalk formation and retinal differentiation, which correlates with optic nerve and foveal hypoplasia observed with human Pax6 gene mutations.…”
Section: Ocular Neural Crest Derivatives: Lessons From Rare Ocular DImentioning
confidence: 99%
See 1 more Smart Citation
“…In zebrafish, sox10 continues to be expressed within the mandibular and maxillary cartilage during the early larval stage but is absent in juveniles [ 11 ]. While sox10 positive cells enter into the developing eye, its expression is short-lived and it is unclear to which ocular tissues these neural crest cells contribute [ 11 , 32 ]. In humans, autosomal dominant nonsense and frame shift mutations in SOX10 , are associated with Waardenburg syndrome, which is primarily characterized by pigmentation abnormalities and mild facial dysmorphism [ 151 , 152 ].…”
Section: Charge Syndrome Associated Genesmentioning
confidence: 99%
“…In zebrafish, neural crest cells migrate in at least three waves. Recent studies have shown that there are two distinct sox10 -positive cell populations that migrate into the eye 12–18 h after neural crest delamination and a subsequent foxd3 -positive cell population that migrates into the anterior segment in the late embryonic and early larval stages [ 11 , 32 ]. Following migration into the anterior segment, signals that regulate terminal neural crest cell differentiation are less well-understood and additional work is needed to identify these gene regulatory networks [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%